1973
DOI: 10.1136/hrt.35.5.480
|View full text |Cite
|
Sign up to set email alerts
|

Study with reflected ultrasound of patients with mitral valve repair.

Abstract: As part of a follow-up investigation in mitral annuloplasty by reflected ultrasound, 39 studies have been carried out in I5 patients who underwent mitral valve reconstructive operations. The rate of diastolic toward closure movemeiit from point E (EF speed) and total amplitude did not correlate with the final valve orifice dimension obtained at operation. Mitral stenosis and incompetence were shown within the first 6 months after repair. Such a noninvasive technique is therefore regarded as an additional metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
5
0

Year Published

1973
1973
1981
1981

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
3
5
0
Order By: Relevance
“…In the assessment of the functional severity of mitral stenosis the echocardiogram has so far made no definite contribution. Several investigators (Edler, 1967;Effert, 1967;Gustafason, 1967) proposed that the diastolic closure rate based on the EF slope of the anterior leaflet of the mitral valve reflects the severity of mitral stenosis but, like others (Mary et al, 1973;Cope et al, 1975), we found it to be insensitive and often misleading in individual patients. We report here a new index of mitral valve closure, derived from the rate at which the anterior and posterior leaflet echoes approximate, which correlates with the severity of the mitral stenosis sufficiently well to be of clinical value.…”
supporting
confidence: 45%
“…In the assessment of the functional severity of mitral stenosis the echocardiogram has so far made no definite contribution. Several investigators (Edler, 1967;Effert, 1967;Gustafason, 1967) proposed that the diastolic closure rate based on the EF slope of the anterior leaflet of the mitral valve reflects the severity of mitral stenosis but, like others (Mary et al, 1973;Cope et al, 1975), we found it to be insensitive and often misleading in individual patients. We report here a new index of mitral valve closure, derived from the rate at which the anterior and posterior leaflet echoes approximate, which correlates with the severity of the mitral stenosis sufficiently well to be of clinical value.…”
supporting
confidence: 45%
“…We agree with previous authors (Mary et al, 1973;Cope et al, 1975;Shiu, 1977) that the EF slope of the anterior mitral leaflet echo is an unreliable index of the severity of mitral stenosis. On the other hand, in the present study the rate of change of left ventricular dimension reflected the functional haemodynamic disturbance in mitral stenosis.…”
Section: Discussionsupporting
confidence: 92%
“…Several investigators (Segal et al, 1966;Edler, 1967;Effert, 1967;Gustafson, 1967) have claimed that the diastolic EF slope of the anterior mitral leaflet reflects the severity of mitral stenosis. As has previously been reported by others (Mary et al, 1973;Cope et al, 1975;Shiu, 1977), we also have frequently noticed discrepancies in patients with mitral stenosis between echocardiographic data and data obtained invasively by cardiac catheterisation and angiography. We have found that the EF slope is not a sensitive measure of the severity of mitral stenosis and is often misleading in individual patients.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Twelve of the 28 patients had pure or predominant mitral regurgitation and 16 had mixed mitral valve disease. All the patients had open mitral annuloplasty (Wooler et al, 1962), the indications for which have been previously described (Mary et al, 1973). In addition to mitral annuloplasty, one patient required plication of the posterior leaflet and one closure of an atrial septal defect.…”
mentioning
confidence: 99%